Metode One Time Pad sebagai Verifikasi Akun E-Wallet dalam Pencegahan Cybercrime - Sarifah, Sarifah; Faisal, Ilham; Lubis, Imran (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to improve security when every time a user logs in or makes a transaction, an OTP (One time pad) will be sent via email, the OTP code is generated randomly and can only be accessed by the account party that has a valid and valid OTP key at that time. certain. Using the one time pad algorithm provides a very high level of security, because the resulting OTP is unique for each transaction. However, its implementation requires strict discipline in key management and proper encryption or decryption processes so that it can function optimally. This system is designed for account user security to prevent data leaks, thereby minimizing the potential for crimes such as identity theft and fraud. The research results show that not a single OTP was repeated in the 10 transactions carried out. Each OTP code generated is unique and different from previous OTPs, both on successful and failed transactions, proving the effectiveness of the system. This website was created using Visual Studio Code to ensure a stable and efficient system implementation